Pruning the Community Orchard: Methods for Navigating Human-Fruit Tree Relations. Issue 1 (2nd January 2020) - Betz, Megan
ABSTRACT: The Bloomington Community Orchard's volunteers articulate their experience in the orchard as working in tandem with human and nonhuman others. Orchardists and fruit trees co-construct the space, and in turn the community it fosters. This co-construction is most prominent in pruning, the most affect-laden task in the orchard's management, requiring violence and care as orchardists carve trees into shape. To understand these human-fruit tree relations and allow my methods to mirror the orchardists' articulation of their experience, I turn to multispecies research, examining how humans speak for or with trees, as well as how trees exert themselves and define a community orchard's needs. I combine participant observation, semistructured interviews, and discourse analysis with a national survey of community orchards and an analysis of trees' responses to orcharding methods to understand how fruit tree-human relations inform the community that emerges from such orchards.